Seventh Session of the governing body, Kigali, Rwanda, 30 October – 3 November 2017. Supplementary Information for CGIAR Report: Plant breeding impacts, non-monetary benefit-sharing and contributions to farmers’ rights - CGIAR (2017)
Document available at: http://www.fao.org/3/a-bs785e.pdf